2005
DOI: 10.1124/jpet.105.092999
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Consumption Enhances Phenylephrine-Induced Contraction in the Isolated Rat Aorta

Abstract: Changes in reactivity to phenylephrine in aortas isolated from 2-, 6-, and 10-week ethanol-treated rats and their age-matched control and isocaloric rats were investigated. Chronic ethanol consumption enhances the contractile response of endothelium-intact and -denuded rat aortic rings to phenylephrine, a response that is time-independent. Pretreatment with indomethacin reduced E max for phenylephrine in denuded aortas from ethanol-treated rats but not control or isocaloric rats. After indomethacin treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 20 publications
1
33
1
4
Order By: Relevance
“…Much of the research on the effects of ethanol on the cardiovascular system has dealt with vascular responsiveness to vasoconstrictor agents (Strickland and Wooles, 1988;Hatton et al, 1992). Several groups have reported enhanced vascular reactivity to vasoconstrictor agents (Pinardi et al, 1992;Tirapelli et al, 2006) or impairment of the vascular relaxation (Kähönen et al, 1999) with regard to cardiovascular complications associated with ethanol consumption.…”
mentioning
confidence: 99%
“…Much of the research on the effects of ethanol on the cardiovascular system has dealt with vascular responsiveness to vasoconstrictor agents (Strickland and Wooles, 1988;Hatton et al, 1992). Several groups have reported enhanced vascular reactivity to vasoconstrictor agents (Pinardi et al, 1992;Tirapelli et al, 2006) or impairment of the vascular relaxation (Kähönen et al, 1999) with regard to cardiovascular complications associated with ethanol consumption.…”
mentioning
confidence: 99%
“…A similar suggestion was advanced by Zhang et al [11] , who suggested that extracellular Ca 2+ is necessary for ethanol to induce contractions [11] . In addition, Tirapelli et al also suggest that the enhanced vascular response to phenylephrine in the aortas of ethanoltreated rats is maintained by an increased extracellular Ca 2+ influx [12] . The results of Walter and Messing are in line with our data [13] .…”
Section: Discussionmentioning
confidence: 99%
“…25) In this study, aortic rings were pre-incubated with 2-APB, and the vasorelaxation caused by CAA were not significantly affected, either in Krebs solution or Ca 2+ -free conditions. Tirapelli 26) has found that IP 3 causes intracellular Ca 2+ release after PE treatment, which does not contribute to the response of alcohol-treated aortic rings. These may undergo PE binding to the IP 3 receptor channel and release Ca 2+ from SR and cause the aortic rings to contract.…”
Section: Ca 2+ Channel Blockers Reduce Caa-induced Vasorelaxationmentioning
confidence: 99%